PENERAPAN PSAK SYARIAH DAN KOMPETENSI AKUNTAN SYARIAH TERHADAP KUALITAS LAPORAN KEUANGAN LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Aditya Achmad Fathony; Iseu Anggraeni; Dani Rachman; Ayu Patmawati (Politeknik Negeri Ambon, 2026)
Introduction: The rapid growth of the global Islamic finance industry, which reached US5.98 trillion in 2024, and Indonesia's Islamic finance industry, which recorded assets of IDR 2,972.94 trillion as of June 2025, has increased the need for effective implementation of Sharia Financial Accounting Standards (PSAK Syariah) and competent sharia accountants to ensure that financial reports remain relevant, reliable, and comparable. This study examines the effect of PSAK Syariah implementation on financial reporting quality, both directly and through sharia accountant competence as a mediating variable, grounded in Human Capital Theory.Methods: This study employs a quantitative approach with an explanatory, cross-sectional design. Primary data were collected through a 1–5 Likert-scale questionnaire administered to accountants and finance staff at Islamic financial institutions in Indonesia, selected using purposive sampling, and analyzed using multiple linear regression and the Sobel Test.Results: Multiple regression analysis shows that PSAK Syariah implementation has a positive and significant effect on sharia accountant competence (t = 269.29; p = 0.000), and sharia accountant competence has a positive and significant effect on financial reporting quality (t = 17.934; p = 0.000). However, PSAK Syariah implementation does not have a significant direct effect on financial reporting quality (t = -1.927; p = 0.059 > 0.05). The Sobel Test result indicates a significant indirect effect (t = 17.97; p = 0.000), confirming that sharia accountant competence fully mediates the relationship between PSAK Syariah implementation and financial reporting quality.Conclusion: PSAK Syariah implementation does not automatically improve the financial reporting quality of Islamic financial institutions unless accompanied by improved sharia accountant competence as the key bridging factor. This study underscores the importance of strengthening continuous education, training, and certification for sharia accountants so that the implementation of sharia accounting standards genuinely translates into financial reporting quality that is transparent, reliable, and sharia-compliant. Keywords: Financial Reporting Quality; Financial Institutions; Human Capital Theory; Islamic Financial Institutions; PSAK Syariah; Sharia Accountant Competence